PENGARUH ELECTRONIC WORD OF MOUTH DAN BRAND IMAGE TERHADAP PURCHASE DECISION (STUDI PADA SALAH SATU HOTEL BINTANG 5 DI BALI) - I Ketut Santra (Politeknik Negeri Samarinda, 2021)
The increasing development of technology now allows everyone to be able to communicate with each other and exchange information with each other without having to meet face to face this is often called electronic word of mouth (eWOM). eWOM has a strong effect on the process of building trust and causing probabilities in purchasing decisions. Besides the brand image of a product or company also plays an important role in purchasing decisions. This study aims to determine the effect of Electronic Word of Mouth and Brand Image on Purchase Decision at one of the 5 star hotel in Bali. Data collection methods used in the form of distributing questionnaires using purposive sampling with 68 respondent. The method used in this research is regression multiple tests processed with SPSS 21.0 software. The results showed that Electronic Word of Mouth and Brand Image partially and simultaneously had an effect on Purchase Decision.Keyword : electronic word of mouth, eWOM, brand image, purchase decision.